2018
DOI: 10.12688/f1000research.13171.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress or infection on rat behavior show robust reversals due to environmental disturbance

Abstract: Background: The behavior of animals is intricately linked to the environment; a relationship that is often studied in laboratory conditions by using environmental perturbations to study biological mechanisms underlying the behavioral change.  Methods: This study pertains to two such well-studied and well-replicated perturbations, i.e., stress-induced anxiogenesis and Toxoplasma gondii -induced loss of innate fear. Here, we demonstrate that behavioral outcomes of these experimental manipulations are contingent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It is high for a medium concentration of urine but low for very low and for very high concentrations of urine. Moreover, recently published results showed that the direction and size of the effect of toxoplasmosis on pleasantness of the cat urine smell could depend on some unknown environmental factor(s) [33]. It will be necessary to include several concentrations of cat urine into future studies and examine in detail the effects of sex-toxoplasmosis-concentration interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is high for a medium concentration of urine but low for very low and for very high concentrations of urine. Moreover, recently published results showed that the direction and size of the effect of toxoplasmosis on pleasantness of the cat urine smell could depend on some unknown environmental factor(s) [33]. It will be necessary to include several concentrations of cat urine into future studies and examine in detail the effects of sex-toxoplasmosis-concentration interaction.…”
Section: Discussionmentioning
confidence: 99%